Perception, Acceptance and Uptake of Human papillomavirus Vaccine among Female Adolescents in Selected Secondary Schools in Ibadan, Nigeria (2017)
Infection with Human papillomavirus (HPV) contributes to malignant changes in the cervix leading to cancer mortality among women. HPV vaccine is now available for its prevention, yet the level of uptake is low. The study aimed at determining Perception, Acceptance and Uptake of Human papillomavirus Vaccine among female adolescents in selected secondary schools in Ibadan, Nigeria. This cross-sectional study was conducted among 296 female adolescent senior secondary school students in Ibadan, Nigeria. Respondents were selected using purposive sampling method and data were collected using self-administered questionnaire. The data were analysed using the Statistical Package for Social Sciences version 20.0. Variables were presented as frequency tables and hypotheses were tested using chi-square and Fisher's exact test at P≤ 0.05. Most 142(48.0%) of the respondents were between ages 15-17. The respondents' perception and knowledge about HPV vaccine, HPV infection and cervical cancer was generally poor. Furthermore, only 12(4.1%) of the respondents have received the HPV vaccine before the study. There is a significant association between adolescent's perception and uptake of HPV vaccine p=0.000 as well as Perception and readiness for the use of HPV vaccine (p=0.007). Parental approval and readiness for HPV vaccine uptake were found to be significantly associated (p=0.000). Since knowledge about Human Papilloma Virus Vaccination is quite low, there is need to increase awareness about the Vaccination among female adolescents and their mothers. Also, peer educators in schools can be trained to improve awareness in schools so as to reduce the incidence of cervical cancer.